Chopin in the music culture of Russia in the second half of the nineteenth century. From Glinka to Scriabin - Baranowski, Tomasz (Interdisciplinary Studies in Musicology, 2018)
This article deals with the reception of Chopin’s music in Russia during the second half of the nineteenth century, as broadly understood. The Chopin cult that developed in Russia was not only genuine, it was exceptional in Europe, giving rise to numerous artistic achievements in many complementary areas, above all composition, pianism and music publishing. The author discusses the issue from an historical perspective, presenting profiles of six outstanding Russian composers in whose life and work the influence of Chopin was at its greatest. The first is Mikhail Glinka, a pioneer of the national orientation in Russian music, who drew abundantly on Chopinian models. The next generation is represented by Anton Rubinstein, the most famous Russian pianist of his times, and two of the Mighty Handful, Mily Balakirev and Nikolay Rimsky-Korsakov. Among the last heirs to Chopin in Russia, pursuing their artistic careers around the turn of the twentieth century, are two composers who masterfully assimilated the stylistic idiom of the composer of the Polonaise-Fantasy, namely Anatoly Lyadov, known as the “Russian Chopin”, and Alexander Scriabin.